Energy crisis 2050?: global scenario and way forward for Malaysia - Mariun, Norman (Universiti Putra Malaysia Press, 2011)
To meet the energy demand of all households worldwide, energy supplies must double by 2050. While fossil fuels will continue to account for the largest proportion of primary energy requirements through the next four decades, we cannot only double world energy supplies and improve access but also effectively manage greenhouse gas emissions. Our core fossil fuel sources - oil, coal and gas - are finite natural resources, and it is being depleted at a rapid rate. The main driver to address this dual challenge will be higher energy prices. Higher prices will propel the developed world towards greater renewable and Nuclear Energy (NE) and attract higher level of energy efficiency. Many developed countries have an ambitious vision that to be powered by 100% Renewable Energy (RE) sources by the middle of this century. In many senses NE is clean. But there is always an argument whether NE is an alternative to fossil fuels and a way to fight global warming. There is much public fear about NE, fuelled by accidents such as Chernobyl, Three Mile Island and very recently Fukushima Daiichi. It is, however, an issue which is becoming more important as we approach a time when fossil fuel resources may run out, making it necessary to find quick and secured alternative sources. Technology enhancement in nuclear reactor and efficient use of nuclear fuel can lessen the risk of NE.The world needs to seriously consider what will be required for transition to a sustainable energy future, and to find solutions to the dilemmas – meet energy demand and mitigate global warming simultaneously. Answering these challenges - the solutions to the energy needs of current and future generations - is one of the most important, challenging and urgent political tasks ahead